Exercise Right Heart Catheterisation in Cardiovascular Diseases: A Guide to Interpretation and Considerations in the Management of Valvular Heart Disease. Issue 1 (2021) - Valle, Felipe H; Mohammed, Basma; Wright, Stephen P; Bentle, Robert; Fam, Neil P; Mak, Susanna
No abstract available